(untitled) (Research, Society and Development, 2021)
Corporate psychopaths reflect negatively on socioprofessional relationships, which also affects the entire productivity of an organization. The psychopath is a shrewd individual with no conscience. His main focus is to have status, control, and power over the company. In view of this fact, we realize the need to study the subject, bringing in a more detailed and objective way the profile of the psychopath, the modus operandi, the damage caused to the victim, and the legal implications of his actions. To this end, a qualitative approach was used, as well as bibliographic and documental research, collecting data from books, periodicals, and scientific articles that match the theme.